Infantile hemangioma in a V2 distribution: Treatment with nadolol - Mariah Giberson; Robert Hayes (Journal of Family Medicine and Primary Care, 2015)
Infantile hemangiomas are common benign tumours of infancy affecting up to 10% of children. They are typically not present at birth but undergo a rapid proliferation stage and then plateau in growth before resolving spontaneously. Recently, beta-blockers have been favoured over systemic corticosteroids for treatment of disfiguring or life-threatening infantile hemangiomas. We present a case of an 11-week-old female with a 7 week history of an evolving hemangioma along a facial V2 distribution. Physical exam revealed a well-defined bright red plaque over the right zygoma and lower eyelid. MRI, echocardiograph, and liver ultrasound were normal. Patient was treated with nadolol and had a rapid and substantial regression of the hemangioma. Nadolol is an effective treatment option for disfiguring facial infantile hemangioma. The use of beta-blockers as treatment offers clues into the pathogenesis of infantile hemangioma, which is not yet completely understood